Application of QuizWhizzer-based Educational Games to Improve Students' Learning Outcomes on History Lessons - Triyoga, Agus; Hartati, Umi; Dewi, Tiara Anggia; Martinaningrum, Martinaningrum (Swarnadwipa, 2024)
This study examines the implementation of QuizWhizzer-based educational games in history learning for class X.7 at SMA Negeri 2 Metro. The main objective is to improve student learning outcomes through more interactive and engaging methods. Using the Classroom Action Research (CAR) method, this study was conducted in two cycles, involving 36 students. Data were collected through observation, interviews, documentation, and tests. The results show a significant increase in student engagement and learning outcomes. In the initial test, only 22% of students achieved the Minimum Completeness Criteria (KKM). After implementing QuizWhizzer, the completion rate increased to 53% in cycle I and 94% in cycle II. Observations indicated a 30% increase in student engagement and higher learning motivation. This study concludes that the use of QuizWhizzer as a learning medium is effective in enhancing student engagement, motivation, and learning outcomes in history subjects. These findings support the adoption of educational games as an innovative and effective learning strategy.